The Vision of Global Maritime Fulcrum within ASEAN Centrality to Maintain Regional Stability - D Triwahyuni; W Dermawan; P Millena (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to discuss the vision of Global Maritime Fulcrum precisely for Indonesia’s foreign policy in the region. This study also in addition to examine the essential needs for coherence and collective response of ASEAN toward strategic rivalries US-China, then bring great risk in the vicinity, notably territorial disputes in South China Sea and following with the logical consequence of the Quad. By using the theory of Regional Security Complex by Barry Buzan, primary and secondary data related to Indonesia’s GMF in the regional architecture were processed using qualitative methods. This study also links the concept of dynamic equilibrium by Indonesia then-Foreign Minister, Marty Natalegawa, which emphasized trust and norms among all actors who were involved in the region, of which aligned with ASEAN centrality. The research result leads to the capability of Indonesia which implies if Indonesia is keen to improve its capabilities through the GMF, this vision can be considered as a tangible complementary and modality in the midst of emerging turbulence power in the region